Aero-structural design and optimization of 50 MW wind turbine with over 250-m blades. Issue 1 (February 2022) - Yao, Shulong; Chetan, Mayank; Griffith, D Todd; Escalera Mendoza, Alejandra S; Selig, Michael S; Martin, Dana; Kianbakht, Sepideh; Johnson, Kathryn; Loth, Eric
The quest for reduced levelized cost of energy has driven significant growth in wind turbine size; however, larger rotors face significant technical and logistical challenges. The largest published rotor design is 25 MW, and here we consider an even larger 50 MW design with blade length over 250 m. This paper shows that a 50 MW design is indeed possible from a detailed engineering perspective and presents a series of aero-structural blade designs, and critical assessment of technology pathways and challenges for extreme-scale rotors. The 50 MW rotor design begins with Monte Carlo simulations focused on optimizing carbon spar cap and root design. A baseline design resulted in a 250-m blade with mass of 502 tonnes. Subsequently, an aero-structural design and optimization were performed to reduce the blade mass/cost with more than 25% mass reduction and 30% cost reduction by determining optimal blade chord and airfoil thickness for best aero-structural performance.